Two connected models for varying amplitudes in BTA-deep-hole-drilling - P. Laurie Davies; Winfried Theis; Claus Weihs (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2005)
Two models are proposed to roughly approximate the observed behavior of the amplitude of the drilling torque in the BTA-deep-hole-drilling process. It is schown that these models are closely connected.
Keywords: 519